ANALYSIS OF RICE PLANT GROWTH (Oryza Sativa) IN POND (PLANTING MEDIA) AT VEGETATIVE STAGE IN LAVERNA GUNUNGSITOLI - Bawamenewi, Tuti Ariani; Gulo, Septin Melindra; Zendrato, Intan Novibriani; Harefa, Oferlina; Zendrato, Della Howu Howu; Gulo, Lilis Sartika; Zega, Priska Rahmat Yanti (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
This study aims to analyze the early growth of rice plants (Oryza sativa L.) at the vegetative stage, which are planted in ponds as an alternative medium in Laverna, Gunungsitoli, to address the challenge of limited rice field land. The method used is descriptive quantitative, with the observed parameters including plant height, number of stems, and number of leaves measured on days 7, 15, and 22 after planting. Samples were taken from 10 plants out of a total population of 35 planting holes with 5 stems per hole. The research results show a significant increase in growth during the observation period. The height of the plants increased from an average of 12 cm on day 7 to 29 cm on day 22. The number of stems also showed growth, from an average of 2.5 stems to 2.8 stems per plant. Meanwhile, the number of leaves increased more significantly from 5 to 11 leaves. However, this growth is not without challenges, especially the attack of golden apple snails (Pomacea canaliculata) which caused some plants to lose leaves and stems, and even die in some cases. However, the growth of the plants is supported by the pond conditions that provide stable moisture, as well as the presence of microorganisms in the growing medium that contribute to nutrient availability. This study concludes that pond cultivation systems have the potential to be an efficient alternative for rice farming in terms of water usage and adaptability to climate change, provided they are accompanied by pest management and the selection of appropriate varieties. Thus, this system can be developed as a sustainable agricultural solution in areas with limited rice field land, such as coastal regions and river basins. These findings are expected to serve as a foundation for further research as well as practical guidelines for farmers and stakeholders in the agricultural sector.